An Giang University journal of science (An Giang University, 2015)
Contents: An investigation of foreign exchange risk management by exporting Vietnamese small and medium sized enterprises; Prevention of environmental pollution - solution for sustainable development of industrial parks in Binh Duong province; Factors influencing the production efficiency of commercial channa micopeltes raising models in Tra Cu district, Tra Vinh province;...